Dynamics of Difficulties Experienced by Prospective Teachers of Psychology During Teaching Practice - Saikauskienė, Albina; Lazdauskas, Tomas (Pedagogika, 2017)
In the opinion of authors involved in studies on teacher education, teaching practice is an essential period of professional development (Hormenu et al., 2014; Hussain et al., 2013; Kirbulut & Bektas, 2011) and personality transformation (Schoeman & Mabunda, 2012) that enables student teachers to develop their professional and classroom identity as well as strengthening knowledge of theory and practice (Lakateb, 2016; Morales Cortés, 2016). Therefore, an analysis of the experience gained during each practice, as well as its dynamics, is undoubtedly useful in developing an active response to the difficulties faced by the student teachers and in adjusting the training process in a way that convinces them they are sufficiently prepared to overcome these difficulties. This study is an analysis of the difficulties faced by prospective teachers of psychology during their teaching practice and the dynamics of such difficulties. We have analysed the reflections of two teaching practices of the previous two years undergone by the same student teachers (n = 34). In the study, we applied qualitative and quantitative data analysis methods. The analysis of the results shows that during the practice students usually doubt their skills and competences in confronting difficulties in classroom management such as first contact with pupils, attention management, involvement in activities, response to misbehaviour, maintenance of discipline etcetera. The quantitative analysis of the confronted difficulties shows that the proportion of the experienced difficulties does not change from one practice to another (McNemar test χ2 < 3.84). More than half (56 %) of students pointed out the same difficulties faced during the first and the second practice. Although some student teachers assess their pedagogical competence as improved, it remains unclear why a meaningful reduction of the difficulties reported after the first practice does not take place in the second practice. The results suggest more research is needed into the dynamics of difficulties experienced by student teachers and into planning new ways to develop professional competences.